Using network partnerships in management consulting - A. A. Soblirov (Вестник университета, 2022)
The article discusses the use of network partnership in the process of interaction between the consultant and the client in the framework of the search, the client’s receipt of investments and further project support. Traditionally, the process of interaction between the client and the consultant is presented in such a way that only these two parties are the main participants in the consultation process. The article discusses the experience of building a multidisciplinary complex consulting process, in which many participants are involved. This experience is based on the practice of the Business Angels of Russia network community. This article analyses the practice of mainly small consulting organisations that are very different from large ones and provide significantly more customised services. The consulting related to investing funds in the client’s business is in the author’s focus. At the same time, only clients belonging to small and medium-sized enterprises naturally stand out in the work. As a rule, they do not seek advice from wellknown and renowned brands in the field of consulting services. As a rule, they do not have enough money for their services, and large consulting firms themselves choose mainly large clients to work with.